Visual assessment of movement quality: a study on intra- and interrater reliability of a multi-segmental single leg squat test - John Ressman; Wilhelmus Johannes Andreas Grooten; Eva Rasmussen-Barr (BMC Sports Science, Medicine and Rehabilitation, 2021)
Abstract Background The Single Leg Squat test (SLS) is a common tool used in clinical examination to set and evaluate rehabilitation goals, but there is not one established SLS test used in the clinic. Based on previous scientific findings on the reliability of the SLS test and with a methodological rigorous setup, the aim of the present study was to investigate the intra- and interrater reliability of a standardised multi-segmental SLS test. Methods We performed a study of measurement properties to investigate the intra- and interrater reliability of a standardised multi-segmental SLS test including the assessment of the foot, knee, pelvis, and trunk. Novice and experienced physiotherapists rated 65 video recorded SLS tests from 34 test persons. We followed the Quality Appraisal for Reliability Studies checklist. Results Regardless of the raters experience, the interrater reliability varied between “moderate” for the knee variable (ĸ = 0.41, 95% CI 0.10–0.72) and “almost perfect” for the foot (ĸ = 1.00, 95% CI 1.00–1.00). The intrarater reliability varied between “slight” (pelvic variable; ĸ = 0.17, 95% CI -0.22-0.55) to “almost perfect” (foot variable; ĸ = 1.00, 95% CI 1.00–1.00; trunk variable; ĸ = 0.82, 95% CI 0.66–0.97). A generalised kappa coefficient including the values from all raters and segments reached “moderate” interrater reliability (ĸ = 0.52, 95% CI 0.43–0.61), the corresponding value for the intrarater reliability reached “almost perfect” (ĸ = 0.82, 95% CI 0.77–0.86). Conclusions The present study shows a “moderate” interrater reliability and an “almost perfect” intrarater reliability for the variable all segments regardless of the raters experience. Thus, we conclude that the proposed standardised multi-segmental SLS test is reliable enough to be used in an active population.